Genome based screening of epitope ensemble vaccine candidates against dreadful visceral leishmaniasis using immunoinformatics approach. (November 2019) - Singh, Garima; Pritam, Manisha; Banerjee, Monisha; Singh, Akhilesh Kumar; Singh, Satarudra Prakash
Abstract: Visceral leishmaniasis (VL) is a dreadful protozoan disease caused by Leishmania donovani that severely affects huge populations in tropical and sub-tropical regions. The present study reports an unbiased genome based screening of 4 potent vaccine antigens against 8023 L. donovani proteins by following the criteria of presence of signal peptides, GPI-anchors and ≤1 transmembrane helix using advanced bioinformatics tools viz. SignalP4.0, PredGPI and TMHMM2.0, respectively. They are designated as genome based predicted signal peptide antigens (GBPSPA). The antigenicity/immunogenicity of chosen vaccine antigens (GBPSPA) with 4 randomly selected known leishmanial antigens (RSKLA) was compared by simulation study employing C-ImmSim software for human immune responses. This revealed better immunological responses. These antigens were further evaluated for the presence of B- and T-cell epitopes using immune epitope database (IEDB) based recommended consensus method of MHC class I and II tools. It was found to forecast CD4 + and CD8 + T-cell responses in genetically diverse human population worldwide as well as different endemic regions through IEDB based predicted population coverage (PPC) analysis tool. The worldwide percent PPC value of combined (HLA class I and II) epitope ensemble forecast was found to be 99.98, 99.96 and 50.04, respectively for GBPSPA, RSKLA and experimentally known epitopes (EKE) of L. donovani . Therefore, these potential antigens/epitope ensembles could favor the design of prospective and novel vaccine constructs like self-assembled epitopes as nano vaccine formulations against VL. Overall, the present study will serve as a model framework that might improve the effectiveness of designed vaccine against L. donovani and other related pathogens. Highlights: Genome based screening of potential antigens against Leishmania donovani using reverse vaccinology approach. Immune simulation study of genome derived antigens with randomly selected known antigens . Epitope ensembles showed significantly higher worldwide coverage (99.98%) over known epitopes of L. donovani (50.04%). Assessment of immunological properties of epitope ensembles pertaining to eliciting host immune response and safety.